Study on long-term uniaxial compression creep mechanical behavior of rocksalt-mudstone combined body. (February 2022) - Lyu, Cheng; Liu, Jianfeng; Ren, Yi; Liang, Chao; Zhang, Qiangxing
Rocksalt and mudstone are usually under common stress in salt storage caverns, resulting in different mechanical properties from pure rocksalt and mudstone. To accurately obtain the creep mechanical characteristics of rocksalt-mudstone combined body, we have made three different combinations. The long-term creep experiment of bedded rocks can more closely reflect the long-term mechanical behavior of surrounding rock of salt storage caverns. The experimental results indicated that the long-term creep curve of the combined body includes initial and steady creep stages, and even includes accelerated creep stage. The strain of mudstone layer in the combined body was lower than that of rocksalt because of the higher strength. With the increase of the height ratio of mudstone, the creep strain of the combined body and each rock layer decreased, but the creep rate increased. A new nonlinear creep-damage constitutive model was proposed, which can well describe the creep evolution characteristics of the experiment. Compared with the fitting curves of classical Burgers and Nishihara creep constitutive models, it is revealed that the proposed model is most consistent with the experimental data. The duration of the long-term creep experiment under lower stress has a highly significant effect on the accuracy of predicting rock creep results. This research will contribute to a deeper understanding of the long-term creep characteristics of bedded rocks in salt storage caverns.